Assessment of the Growth Performance by RNA:DNA Ratio in Cyprinus carpio var. communis (Scale carp) Using Different Dietary Protein Levels - Bhat, Hussna; Ahmad, Irfan; Asmi, Oyas; Shah, Feroz; Bhat, Bilal; Hussain, Tarik (International Journal of Bio-resource and Stress Management, 2022)
The study was conducted at wet laboratory of Faculty of Fisheries, Rangil, Ganderbal, SKUAST-Kashmir, India from the time period of March to June, 2019 on scale carp fingerlings (Cyprinus carpio var. communis) to determine the growth performance by measuring RNA:DNA ratio in scale carp after fed with dietary protein level. The fingerlings were fed with three different levels of silkworm pupae supplement [17.51 g 100 g-1 (T1), 14.42 g 100 g-1 (T2), 11.33 g 100 g-1 (T3)] and a control in which no silkworm pupae was included. RNA:DNA ratio were highest in T1 (1.609), followed by T2 (1.526) and T3 (1.239) while the control showed the lowest ratio (0.929). Similarly, fingerlings fed with Silkworm pupae supplemented diets (T1, T2 and T3) exhibited relatively better growth in terms of body weight gain, % weight gain, specific growth rate (SGR), feed conversion ratio (FCR) and protein efficiency ratio (PER) as compared to the control. The highest weight gain of 2.4 g was recorded in T1 followed by T2 (2.09 g) and T3 (1.52 g) while the control achieved the lowest weight gain of 0.72 g. Overall, the results revealed that T1 performed better as compared to the rest treatments and control. In general, the RNA:DNA ratio and growth results correlate with each other in different treatments and control. So, RNA:DNA ratio seems to be as an effective and rapid indicator of growth performance.